2016
DOI: 10.1007/s15010-016-0960-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV infection with extrapulmonary tuberculosis: a systematic review

Abstract: Purpose HIV/AIDS is a known risk factor for the development of pulmonary tuberculosis (PTB). However, the association is less clear between HIV and extrapulmonary tuberculosis (EPTB). We conducted a systematic review to determine the association between HIV and EPTB. Methods We searched the electronic databases Medline, Embase and relevant conference literature using defined search terms for EPTB and HIV. Only publications in English and only studies reporting adjusted estimates were included while our searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 27 publications
(55 reference statements)
3
36
0
4
Order By: Relevance
“…Fifty-seven per cent of adults in the current study were female, a finding in keeping with previous spinal TB studies from South Africa [7, 8, 25, 26] but in contrast to other large studies in which 51–61% of spinal TB cases were male [4, 11, 12, 24]. One possible explanation for this difference is HIV infection and its oft-cited association with extra-pulmonary TB disease [27, 28]. For example, whereas HIV co-infection was ⩽4% [4, 24] or not reported [11, 12] in the afore-mentioned studies from other parts of the world, 56% of adult females and 36% of adult males with known HIV status in the current study were HIV-positive, indicating a significantly higher HIV-positive prevalence among adult females in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fifty-seven per cent of adults in the current study were female, a finding in keeping with previous spinal TB studies from South Africa [7, 8, 25, 26] but in contrast to other large studies in which 51–61% of spinal TB cases were male [4, 11, 12, 24]. One possible explanation for this difference is HIV infection and its oft-cited association with extra-pulmonary TB disease [27, 28]. For example, whereas HIV co-infection was ⩽4% [4, 24] or not reported [11, 12] in the afore-mentioned studies from other parts of the world, 56% of adult females and 36% of adult males with known HIV status in the current study were HIV-positive, indicating a significantly higher HIV-positive prevalence among adult females in this study.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, 50% of all spinal TB cases were between 23 and 47 years old with a median age of 38 years among adult cases (Table 1). While previous studies from the USA [4] and Eastern Mediterranean [11] reported a somewhat older median age of approximately 50 years among spinal TB cases, the current age distribution is similar to findings from Kenya [24] and China (27) 110 (28) Data are presented as n (%) for non-missing data, unless otherwise indicated, with % values rounded to the nearest whole number. a MRI, magnetic resonance imaging (n = 378); CT, computed tomography (n = 4).…”
Section: Spinal Tb Among Adults In the Western Capesupporting
confidence: 72%
“…The lymph nodes are the most common location of TB after the lungs. 9,10 TB lesions in the oral cavity are rare, 11 and most originate from pulmonary TB, so they can be considered secondary TB. Primary TB in the oral cavity without pulmonary involvement is rare, but it is more commonly found in children and adolescents.…”
mentioning
confidence: 99%
“…Tuberculosis, a curable infectious disease once thought to be a death sentence, still remains as one of the 10 leading causes of death worldwide [1,2]. Lungs were classically the primary target for tuberculosis, but these recent years, extrapulmonary tuberculosis has become more frequent especially with the increase in Human Immunodeficiency Virus (HIV) infection rates [3]. This resulted in a large diversity in clinical presentations.…”
Section: Introductionmentioning
confidence: 99%